2023
DOI: 10.3390/agriculture13020231
|View full text |Cite
|
Sign up to set email alerts
|

Can Nanomaterials Improve the Soil Microbiome and Crop Productivity?

Abstract: Global issues such as soil deterioration, pollution, and soil productivity loss induced by industrialization and intensive agriculture pose a serious danger to agricultural production and sustainability. Numerous technical breakthroughs have been applied to clean up soil or boost the output of damaged soils, but they have failed to restore or improve soil health to desired levels owing to expense, impossibility in a practical setting, or, to a lesser extent, high labor consumption. Recent nanotechnology advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 137 publications
0
16
0
Order By: Relevance
“…Nanoparticles delivered to the plant through the rhizosphere have to pass through diverse microbial biofilms and varying soil factors that influence nanoparticles dissolution, coating, agglomeration, and bioavailability, as corroborated by [83]. Nanoparticles affect the soil environment, triggering nutrient mineralization and mobilization through numerous integrated mechanisms mediated by plant root exudates, soil organic matter, and rhizospheric bacteria [84]. The interplay between nanoparticles and rhizobacteria can improve soil productivity and plant performance under challenging environmental conditions and assist in developing environmentally safe nano-formulations for agricultural applications (Figure 1).…”
Section: Mechanisms Of Nano-microbe Interactionsmentioning
confidence: 99%
“…Nanoparticles delivered to the plant through the rhizosphere have to pass through diverse microbial biofilms and varying soil factors that influence nanoparticles dissolution, coating, agglomeration, and bioavailability, as corroborated by [83]. Nanoparticles affect the soil environment, triggering nutrient mineralization and mobilization through numerous integrated mechanisms mediated by plant root exudates, soil organic matter, and rhizospheric bacteria [84]. The interplay between nanoparticles and rhizobacteria can improve soil productivity and plant performance under challenging environmental conditions and assist in developing environmentally safe nano-formulations for agricultural applications (Figure 1).…”
Section: Mechanisms Of Nano-microbe Interactionsmentioning
confidence: 99%
“…Nano-remediation technology suggests numerous potentials, particularly PAHs polluted soil remediation and reduced other hazardous pollutants for the safe and clean land and overall environmental benefits. The application of nano-remediation technology greatly improved the water and soil quality by reducing pollutants which results high yield products, vegetation, and enhance survival of indigenous microbes (Rajput et al, 2023). Another environmental benefit of using this technology is that it prohibits the leaching of hazardous compounds from the soil to ground water and limits the contamination.…”
Section: Nano-enhanced Microorganisms Mediated Remediation Of Pah Pol...mentioning
confidence: 99%
“…Adding specific substances to the soil enhances its capacity to sustain plant life ( Urra et al., 2019 ; Rubin et al., 2023 ; Kumari et al., 2023b ). Plant growth-promoting rhizobacteria (PGPR) and nanomaterials (NMs) or nanoparticles (NPs) are under consideration as a novel approach to boost crop productivity and soil fertility ( El-Ramady et al., 2022 ; Upadhayay et al., 2023 ; Rajput et al., 2023a ; Kumari et al., 2024 ). Several research studies have demonstrated numerous benefits that soil organic amendments may provide, including better soil texture, higher soil fertility, restored soil health, and, ultimately, higher crop yield ( Urra et al., 2019 ; Rani et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%